Auxiliary consumption: A necessary energy that affects thermoelectric generation. (August 2018) - Aranguren, P.; Araiz, M.; Astrain, D.
Highlights: Study on the incorporation of heat exchangers with liquid as heat carrier into TEGs. Generation reduction of the 40% if auxiliary consumption is taken into account. Importance of including every element of the dissipation system. 128 MWh/year are obtained including a thermosyphon without auxiliary equipment. Abstract: Waste heat recovery can apply to a wide range of applications, from transportation, or industries to domestic appliances. Thermoelectric generation technology applied to those cases could produce electrical energy and thus improve their efficiency. A validated computational methodology, which simulates the behavior of any thermoelectric generator and calculates the energy consumption of the auxiliary equipment involved, has been used to determine the potential of waste heat harvesting. The usable energy, the net energy, generated has to be maximized, not only the thermoelectric generation has to be maximized, but also the consumption of the auxiliary equipment has to be minimized, or if possible eliminated. Heat exchangers with a liquid as the heat carrier procure high thermoelectric generations, as their thermal resistances are very low, nevertheless when the consumption of their auxiliary consumption is borne in mind, their use is not that promising. The optimal thermoelectric energy obtained from the flue gases of a real industry using these dissipation systems is 119 MWh/year, while the maximum net energy is 73 MWh/year due to the consumption of the auxiliary equipment. The latest scenario does not only represent a 40% reduction from the optimal thermoelectric generation but also a different optimal working point. The complete elimination of the auxiliary equipment using novel biphasic thermosyphons with free convection at the same application produces a net energy of 128 MWh/year. This novel dissipation technology presents an increase on the thermoelectric generation due to its low thermal resistances, but above all due to the elimination of the auxiliary consumption.